PEMBERDAYAAN MASYARAKAT DALAM MENJAGA KEBERSIHAN SUNGAI MELALUI PENGGUNAAN TEMPAT SAMPAH TERAPUNG ( FLOATING TRASH CAN ) DI DESA TANJUNG SETEKO KECAMATAN INDRALAYA KABUPATEN OGAN ILIR - Nukmal Hakim (Lembaga Pengabdian pada Masyarakat, 2014)
Empowerment have keeping the River HealthÂ by using the Float Trash Can in Tanjung Seteko Village Indralaya sub distric Ogany Ilir Regency.Â Provide alternative solutions that could be applied in order to overcome the bad habits people taking out the trash into the river. Maintenance of order and cleanliness of the river tributaries in the village of Tanjung Seteko Indralaya District . This activities are expected to provide tangible benefits to the target audience , as: 1 ) . Society has a floating trash . 2 ) . Society will be protected from various diseases caused by waste dumped into the river . The Community Service activities consciousness will arise to always maintain the cleanliness of the river , Trash FloatingÂ is one of the main of the solution in addressing the problems of waste in the water , floating trash can is a design environment technology in the form of floating garbage which is applied through simple methods and technologies to optimize the role of communities around the river in South Indralaya to get used to dispose of waste in place and eliminate bad habits not to throw garbage into the river.